2018
DOI: 10.1186/s13756-018-0300-x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial effect of copper alloys on Acinetobacter species isolated from infections and hospital environment

Abstract: BackgroundAn increased proportion of Gram-negative bacteria have recently been reported among etiologic agents of infection. In Poland, Acinetobacter baumannii is a big problem for hospitals, especially intensive care units. Touch surfaces made from materials with antimicrobial properties, especially copper alloys, are recommended as a supplementary method of increasing biological safety in the hospital environment.Aim of the studyThe objective of this study is to determine the susceptibility to selected coppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…The cell density was expressed as Log 10 of the colony-forming units per mL (Log 10 CFU/mL) and the average values and standard deviations were then calculated and plotted using Prim 7 (GraphPad, San Diego, CA, USA). A bacteriostatic effect was considered to have occurred when the decrease in the inoculum was >2 Log 10 and <3 Log 10 and a bactericidal effect was considered to have occurred when the cell density decrease was ≥3 log 10 [ 13 , 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…The cell density was expressed as Log 10 of the colony-forming units per mL (Log 10 CFU/mL) and the average values and standard deviations were then calculated and plotted using Prim 7 (GraphPad, San Diego, CA, USA). A bacteriostatic effect was considered to have occurred when the decrease in the inoculum was >2 Log 10 and <3 Log 10 and a bactericidal effect was considered to have occurred when the cell density decrease was ≥3 log 10 [ 13 , 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…For example, within the Acinetobacter genus, the reduction in Acinetobacter lwoffii counts on brass obtained after a 5 h exposure were lower (around 99% reduction) than those obtained for Acinetobacter pittii and most A. baumannii strains (99.9% reduction and above) [ 60 ]. At the species level, one XDR A. baumannii strain count was unchanged after a 5 h exposure to brass, while the two other A. baumannii strains (1 MDR and 1 XDR) registered a count reduction of at least 99.9% [ 60 ]. Similarly, out of three MRSA strains, two were readily eradicated from the surface of brass while only a one log (90%) reduction was registered for the third one after a 6 h exposure [ 54 ].…”
Section: In Vitro Antibacterial Activity Of Copper and Brass Alloymentioning
confidence: 99%
“…The antibacterial efficacy is usually assessed after a time of exposure to the copper-containing surface using reduction in bacterial counts either compared to the initial inoculum and/or to the counts obtained on a control surface deprived of antibacterial properties such as glass, plastic or stainless steel (Figure 2). These tests were first held on food pathogens and collection strains susceptible to antibiotics [51][52][53], but publications soon moved on to report significant reductions in bacterial counts on copper and copper alloy surfaces for a range of multidrug-resistant (MDR) bacteria and/or bacteria originating from clinical settings [32,[54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69]. Indeed, the importance of testing clinical strains to evaluate whether any co-selected, cross-selected and/or co-regulated resistance between copper and antibiotics and/or detergent-disinfectants could occur soon appeared as mandatory [62].…”
Section: Vegetative Formsmentioning
confidence: 99%
“…Cu99 showed a bactericidal effect of less than 1 hour for MRSA, 2 hours for P. aeruginosa and exhibited a closer bactericidal range effect against A. baumannii . Rozanska et al [ 15 ] showed antimicrobial effect of copper alloys on Acinetobacter species isolated from infections and hospital environment. And the results of the study confirmed effective activity (bacteriocidal or bacteriostatic) of copper alloys [ 15 ].…”
Section: Discussionmentioning
confidence: 99%